Warning Label and Video Efficacy on High School Student Consumption of Soft Drink and Fast Food - Sumarwan, Ujang; Atilah, Siti; Lestari, Vici Lucyta (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
Excessive consumption of fast food and soft drink causes various negative impacts on health. This study aims to analyze the knowledge and intention toward fast food and soft drinks consumption on adolescents. The design used in this study was pre-experimental in one of senior high schools in Bogor Regency. Samples of this study 96 students and chosen by convinience. Samples are divided into three groups, which are warning label exposure group, the video exposure group, and the control group. Research results show that warning label and video are able to increase knowledge of fast food and soft drinks. In addition, the exposure of the warning label and video also reduced the intention of the sample in consuming fast food and soft drinks. The results of one way ANOVA test showed that the knowledge and intention of the control group differed significantly with the experimental group both with the exposure of warning labels and video. Further testing results of the Post Hoc Test showed that warning label exposure further enhance knowledge than video exposure and without exposure. Warning labels and video effectively reduce the intention to consume fast food and soft drinks.